2022
DOI: 10.1002/mgg3.1929
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and epileptic encephalopathy related to a heterozygous variant of the RHOBTB2 gene: A case report from French Guiana

Abstract: Here we report a case of developmental and epileptic encephalopathy related to RHOBTB2 gene mutation in a ten‐month old infant in French Guiana. Although the 28 previously reported cases had early‐onset epilepsy and severe intellectual disability, here the reported individual presented with late postnatal onset of microcephaly and the absence of cortical atrophy on MRI. The publication of cases of such a rare form of developmental and epileptic encephalopathy will eventually allow us to better understand the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…RHOBTB2 encodes an atypical Rho-related BTB-containing protein 2, a GTPase. Heterozygous variants have been reported to lead to developmental and epileptic encephalopathies, 42 , 43 postnatal microcephaly, intellectual impairment and Rett-like phenotype. 44 Paroxysmal movement disorders, including chorea, dystonia and dyskinesias, were reported in a series of 13 patients.…”
Section: Synaptopathiesmentioning
confidence: 99%
“…RHOBTB2 encodes an atypical Rho-related BTB-containing protein 2, a GTPase. Heterozygous variants have been reported to lead to developmental and epileptic encephalopathies, 42 , 43 postnatal microcephaly, intellectual impairment and Rett-like phenotype. 44 Paroxysmal movement disorders, including chorea, dystonia and dyskinesias, were reported in a series of 13 patients.…”
Section: Synaptopathiesmentioning
confidence: 99%
“…1 and 2). [4][5][6][9][10][11][12][13][14][15][16] The comprehensive analysis of the literature review can be accessed within the Supplementary material S2.…”
Section: Literature Reviewmentioning
confidence: 99%
“…9 Department of Pediatrics, Division of Medical Genetics, Duke Health, Durham, NC, USA. 10 Department of Neuroscience, Rehabilitation, Ophthalmology, Genetics, Maternal and Child Health, University of Genoa, Genoa, Italy. 11 Child Neuropsychiatry Unit, IRCCS Istituto Giannina Gaslini, Genova, Italy.…”
Section: Introductionmentioning
confidence: 99%
“…As comprehensive sequencing of the coding regions of ATP1A3 had not identified a causal mutation, these cases are referred to as ATP1A3-negative, either typical AHC patients or patients with one or more of the hallmark clinical traits observed in the condition (AHC-like). Exome sequencing in parallel studies has shown that rare protein-disrupting variants in ATP1A2 [8,9] and RHOBTB2 [10,11] contribute to AHC, although these collectively explain a very small fraction of cases. Hence we here sought to (1) use targeted whole-gene sequencing of ATP1A3 to look for noncoding pathogenic variants in our cohort of 26 ATP1A3-negative patients, and (2) use exome sequencing to further identify other genes that may be responsible for the observed phenotypes.…”
Section: Introductionmentioning
confidence: 99%